Metabolic syndrome in overweight children from the city of Botucatu - São Paulo State - Brazil: agreement among six diagnostic criteria - Rinaldi, Ana Elisa M.; Pimentel, Gustavo D. [UNESP]; Pereira, Avany F.; Gabriel, Gleice F. C. P. [UNESP]; Moreto, Fernando [UNESP]; Burini, Roberto Carlos [UNESP] (Biomed Central Ltd., 2010)
Background: The metabolic syndrome has been described in children; however, a standard criterion has not been established for its diagnosis. Also, few studies have been conducted to specifically observe the possible existence of agreement among the existing diagnostic criteria. The purpose of the study is to evaluate agreement concerning prevalence rates of the metabolic syndrome diagnosed by six different criteria in overweight schoolchildren in the city of Botucatu - SP - Brazil.Methods: This is a cross-sectional study on 128 overweight schoolchildren. Clinical examination included anthropometry, pubertal staging evaluation, and blood pressure. Triacylglycerol, glycemia, HDL-cholesterol, insulin levels, and HOMA-IR were determined. The Kappa index, the Mann-Whitney test and the chi-square test were used for statistical analysis.Results: The prevalence of the metabolic syndrome varied from 10 to 16.5% according to different diagnostic criteria. Results were similar for boys and girls and pubertal stage. Great agreement was observed among the six different diagnostic criteria for the metabolic syndrome.Conclusions: Different diagnostic criteria, when adopted for subjects with similar demographic characteristics, generate similar and compatible prevalence. Results suggest that it is possible to adopt any of the analyzed criteria, and the choice should be according to the components available for each situation.